Arginine-dependent immune responses - Martí i Líndez, Adrià-Arnau; Reith, Walter (Cellular and molecular life sciences : CMLS, 2021)
A growing body of evidence indicates that, over the course of evolution of the immune system, arginine has been selected as a node for the regulation of immune responses. An appropriate supply of arginine has long been associated with the improvement of immune responses. In addition to being a building block for protein synthesis, arginine serves as a substrate for distinct metabolic pathways that profoundly affect immune cell biology; especially macrophage, dendritic cell and T cell immunobiology. Arginine availability, synthesis, and catabolism are highly interrelated aspects of immune responses and their fine-tuning can dictate divergent pro-inflammatory or anti-inflammatory immune outcomes. Here, we review the organismal pathways of arginine metabolism in humans and rodents, as essential modulators of the availability of this semi-essential amino acid for immune cells. We subsequently review well-established and novel findings on the functional impact of arginine biosynthetic and catabolic pathways on the main immune cell lineages. Finally, as arginine has emerged as a molecule impacting on a plethora of immune functions, we integrate key notions on how the disruption or perversion of arginine metabolism is implicated in pathologies ranging from infectious diseases to autoimmunity and cancer.